THE RELATIONSHIP OF PARENT-CHILD RELATIONSHIP WITH PROBLEMATIC INTERNET USE IN STUDENTS IN PADANG CITY - Dinda Syafvira; Niken Hartati (Causalita, 2025)
This research aims to determine the relationship between parent child relationships and problematic internet use among students in Padang City. The research sample used was 253 new students at Padang State University taken based on random sampling techniques. The instrument used for the problematic internet use variable was developed based on the theory of Caplan (2003), while the parent child relationship variable was developed based on the theory of Dixson, Bermes, & Fair (2014). The validity test of the problematic internet use scale has an item discrimination power of 0.315-0.760, while for the parent child relationship scale it is 0.377-0.832. This research analyzes data using the Pearson Product Moment correlation technique. The results of the research show that the correlation coefficient (r) between parent child relationship and preference for social interaction is -0.670 with a significance of 0.000, between parent child relationship and mood regulation is -0.417 with a significance of 0.000, between parent child relationship and cognitive preoccupation is -0.420 with significance is 0.000, between parent child relationship and compulsive internet use is -0.420 with a significance of 0.000, and between parent child relationship and negative outcome is -0.674 with a significance of 0.000 where (p<0.05). This shows that parent child relationships are negatively correlated with problematic internet use.